Bacillus cereus infection in neonates and the absence of evidence for the role of banked human milk: Case reports and literature review. (July 2019) - Lewin, Antoine; Quach, Caroline; Rigourd, Virginie; Picaud, Jean-Charles; Perreault, Thérèse; Frange, Pierre; Domingo, Marc-Christian; Lalancette, Cindy; Delage, Gilles; Germain, Marc
Abstract: Background: Banked human milk (BHM) has inherent infectious risks, even when pasteurized. Because of the ubiquity of Bacillus cereus in the environment and its ability to resist the Holder pasteurization process, there is a concern that BHM might lead to severe B. cereus infections. Objective: We reviewed observed and published cases to determine the potential causal role of BHM as the source of these infections. Methods: Two infants in the province of Québec (Canada) developed a B. cereus neonatal infection, and both had received BHM. We conducted bacteriological studies to compare clinical isolates and those found in these cases. Results: After extended culture of BHM retention lots, B. cereus was found to have been involved in batches related to the first case. However, molecular typing showed that the strain was different from the clinical isolate, therefore excluding BHM as the source of contamination. In the second case, a Brevibacillus spp was isolated, a species distinct from the clinical isolate. Conclusion: Based on these cases and others reported in the literature, a causal link between B. cereus contaminated BHM and preterm neonatal infection has never been documented. Therefore, the risk that BHM can cause this infection remains theoretical. Given the widespread presence of B. cereus in the hospital environment and its capacity to resist standard cleaning procedures, it seems likely that airborne or direct or indirect contact are the main sources of most, if not all, cases of severe B. cereus neonatal infections, even in babies exposed to BHM.